FINITE ELEMENT MODELING AND ANALYSIS OF A PASSENGER CAR TYRE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Tyre analyses done through experimental methods takes more time as well as cost andalso the development of the new tyre take longer time. To avoid this tidious tyre developmentprocess its behaviour can be predicted through Finite Element analysis. The main objective of thework is to perform finite element analysis of the tyre using Abaqus software. For the analysis I hadchosen 165/70R 14 81S passenger car tyre and Mooney rivilin material model is used For myanalysis. I had used frequency linear perturbation procedure and subspace Eigen solver with themaximum frequency of 20.68 Hz considering the tyre rotates at a speed of 120 Km/hr totally 4000iteration has been used for this analysis. Since tyre is in torus in shape Tetrahedral element can onlyused for meshing.From this analysis we can find six different modes of shape of the tyre andmaximum displacement at different modes. In static and dynamic analysis I have planned to find outthe stress developed in bead part, body ply and tread part